Pengaruh Lingkungan Kerja dan Kompleksitas Tugas Terhadap Kinerja Auditor Dengan Kompetensi Sebagai Variabel Modearsi Pada Inspektorat Daerah Sumatera Selatan - Jaya, Alvin Aditya; Sabrina, Nina; Afrida, Anggrelia (Asosiasi Dosen Akuntansi Indonesia, 2023)
This study aims to determine the effect of the work environment and task complexity on the performance of auditors at the Regional Inspectorate of South Sumatra Province. Sampling using saturated samples, the samples studied were 37 auditors in the Regional Inspectorate of South Sumatra Province. The data needed is primary data obtained through distributing questionnaires to auditors who work at the Regional Inspectorate of South Sumatra Province. The data analysis technique used in this research is validity test, reliability test, classical assumption test and hypothesis test. The results of this study partially indicate that there is an influence between work environment and task complexity on auditor performance. And in moderation, the work environment is a homoglycer of moderation. The complexity of the task is pure moderation. Work Environment has a significant effect on Auditor Performance at the Regional Inspectorate of South Sumatra Province.